IMPLEMENTASI MODEL KURIKULUM KUTTAB DALAM MEMBANGUN PERILAKU KETAUHIDAN SANTRI: Studi Kasus di lembaga pendidikan Kuttab Al Fatih Malang - Izzah, Nurul; Supriyatno, Triyo (Muta'allim: Jurnal Pendidikan Agama Islam, 2023)
This study aims to investigating more deeply the implementation of the Kuttab Al- Fatih Malang curriculum in developing students' onesses of Allah Subhanahu wa Ta’ala behavior. The researcher uses a qualitative field research model with descriptive research method. Through this method and approach, the researcher come right away to Kuttab Al- Fatih Malang to obtain data. To obtain data, the researchers uses instruments, namely: observation sheets, field notes, a voice recorder for interview, and camera to take pictures as documentation. The data obtained are analyzed through the sequences of data collection, data reduction, then interpreting the data, and ended by making conclusions. The result of the study proves that the planning, implementation and evaluation process as a form of managing the Kuttab curriculum are carried out using the concept of Faith before Al Qur'an. The planning of Kuttab activities is designed based on a module that focuses on developing Faith. The way teachers teach at Kuttab refers to the book Ar Rasul al Mu'allim, always instilling muraqabatullah related to his divine values. The implementation of the faith teaching is able to develop onesses of Allah Subhanahu wa Ta’ala behavior so that the students' longing for the Al Qur'an is increasingly formed. The dialogue method of faith and nature is used as washilah in growing the oneness of Allah SWT. behavior of the students through tafakkur of the universe as well as tadabbur of Al Qur’an verses that are adapted to the sub themes-of learning. Meanwhile, the evaluation model in the Kuttab curriculum uses two types of assessment, namely the assessment of courtesy and the assessment of students' understanding. The taking of these two scores is found in the daily score (60%) and the Final Semester Test scores (40%). The form of the questions that are given can be in the form of integration questions and general science. Abstrak Penelitian ini bertujuan untuk menggali lebih dalam implementasi kurikulum Kuttab Al-Fatih Malang dalam membangun perilaku ketauhidan santri. Peneliti menggunakan jenis penelitian lapangan (field research) yang bersifat kualitatif dengan metode deskriptif research. Melalui metode dan pendekatan tersebut peneliti sebagai instrumen utama akan terjun langsung ke Kuttab Al Fatih Malang untuk mendapatkan data melalui observasi, wawancara dan dokumentasi. Data yang didapatkan akan di analisis melalui tahap pengumpulan data, reduksi data, kemudian menginterpretasikan data, dan diakhiri dengan kesimpulan. Hasil penelitian membuktikan bahwa kegiatan perencanaan, proses implementasi dan evaluasi sebagai wujud dari pengelolaan kurikulum Kuttab dilaksanakan menggunakan konsep Iman sebelum Alquran. Perencanaan kegiatan Kuttab dirancang sesuai modul yang berfokus pada penggemburan Iman. Cara mengajar guru di Kuttab merujuk pada kitab Ar Rasul al Mu’allim, selalu menanamkan muraqabatullah terkait dengan tauhidnya. Pengimplementasian pengajaran Iman mampu membangun perilaku ketauhidan sehingga rasa rindu santri kepada Alquran semakin terbentuk. Metode dialog Iman dan alam dijadikan wasilah dalam menumbuhkan tauhid para santri, melalui tafakkur alam dan tadabbur ayat Alquran yang disesuaikan pada subtema pembelajaran. Sedangkan model evaluasi dalam kurikulum Kuttab menggunakan dua jenis penilaian yaitu penilaian adab dan penilaian pemahaman santri. Pengambilan kedua nilai tersebut terdapat dalam nilai harian (60%) dan nilai UAS (40%). Bentuk soal yang diberikan dapat berupa soal integrasi dan per murofaqot.